Relasi Makna dalam Lirik Lagu Lagu Karya Maher Zain (Kajian Semantik) - Ihsan, Muhammad; Putra, Ringgal Oksa (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
This research discusses the relationship of meaning in the lyrics of Maher Zain's songs through a semantic approach. The background of this research lies in the importance of understanding the connection between words and their meanings in song lyrics to gain a deeper understanding of language nuances and how language is used in different contexts. The aim of this research is to analyze the semantic relationships in Maher Zain's song lyrics and provide examples of these semantic relationships in the lyrics. The method used in this research is descriptive-qualitative research, employing an observational method with documentation techniques. The research findings indicate various types of semantic relationships in Maher Zain's song lyrics, such as synonyms, antonyms, homonyms, and hyponyms. Additionally, this research also discusses the analysis of semantic relationships in the lyrics, particularly the presence of polysemy or multiple meanings in certain words. The implications of this research underscore the importance of understanding the semantic relationships in song lyrics to gain a deeper understanding of the message and themes of the songs.